Combined abdominoperineal approach for the management of presacral cyst: a case report and literature review - Tang Yan; Wang Xiaofeng; Ma Hao; Xue Yahong; Fan Zhimin (结直肠肛门外科)
The clinical incidence of presacral cyst is not high, and surgery is the main treatment method. Appropriate surgical approach is crucial for complete excision of presacral cyst, but there is still a lack of mature and unified surgical approach. Currently, the transsacrococcygeal approach is the preferred approach for most anorectal surgeons to treat presacral cyst, while there are few clinical reports on the surgical treatment of presacral cyst using the combined abdominoperineal approach. This paper reports the diagnosis and treatment of a case of presacral cyst treated by combined abdominoperineal approach and shares relevant clinical diagnosis and treatment experience with colleagues.